Organizational Reintegration and Trust Repair after an Integrity Violation: A Case Study - Gillespie, Nicole (Business ethics quarterly, 2014)
This paper presents a holistic, contextualised case study of reintegration and trust repair at a UK utilities firm in the wake of its fraud and data manipulation scandal. Drawing upon conceptual frameworks of reintegration and organizational trust repair, we analyze the decisions and actions taken by the company in its efforts to restore trust with its stakeholders. The analysis reveals seven themes on the merits of proposed approaches for reintegration after an integrity violation (including open investigations, accurate explanations, apologies, penance, and systemic reforms), and novel insights on the role of organizational identity, “changing of the guard” and cultural reforms alongside procedural modifications. The case further supports the dynamic nature of stakeholder salience across the reintegration process. The study both supports propositions from existing frameworks and suggests novel theoretical extensions for future research.